Biofunctionalized peptide-based hydrogel as an injectable scaffold for BDNF delivery can improve regeneration after spinal cord injury. Issue 2 (February 2019) - Hassannejad, Zahra; Zadegan, Shayan Abdollah; Vaccaro, Alexander R.; Rahimi-Movaghar, Vafa; Sabzevari, Omid
Highlights: IKVAV-functionelized peptide amphiphile (IKVAV PA) hydrogel provided a sustained release of BDNF over 21 day in vitro. IKVAV PA hydrogel preserved bioactivity of loaded BDNF while the hydrogel nanostructure changed into aligned nanofibers. In vivo study showed that IKVAV PA hydrogel with or without BDNF caused no inflammatory reaction. Injection of BDNF-loaded IKVAV PA hydrogel resulted in astrogliosis reduction at 6 weeks post-injury. After severe compression injury providing a permissive environment and BDNF was needed for preserving spared axons. Abstract: Background: The complex pathophysiological events occurring after traumatic spinal cord injuries (TSCI) make this devastating trauma still incurable. Peptide amphiphile (PA) hydrogels are nanobiomaterials displaying desirable properties for application in regenerative medicine because they are absorbable, injectable, allowing biofunctionalization, controlling release of trophic factors and mimic extracellular matrix (ECM). In this study, we explored the potentiality of the IKVAV-functionalized PA hydrogel to provide a permissive environment for cell migration and growth as well as sustained release of BDNF at the lesion after severe compression injury model. Methods: The IKVAV-functionalized PA was synthesized by automated solid-phase approach and its secondary structure was evaluated by Circular dichroism (CD) spectroscopy. The potential of IKVAV-functionalized PA to self-assemble into nanofibers and hydrogel formation were assessed using transmission electron microscopy (TEM). Release profiles of BDNF from hydrogel and the bioactivity of the released BDNF from hydrogel were determined using ELISA and DRG bioassay, respectively. Severe spinal cord injury was induced using clip compression at T7-T8 vertebral segment. Twenty four hours post-injury the animals were treated by either IKVAV PA hydrogel, BDNF-loaded IKVAV PA hydrogel, BDNF solution or saline. Two and six weeks later, animals were sacrificed and the lesion site was evaluated based on GFAP, CD68 and ß III tubulin immunoreactivity. Also, locomotor recovery was assessed during 6 weeks using Basso, Beattie, Bresnahan (BBB) scoring test. Results: The IKVAV PA arranged into nanofibrous structure and provided a sustained release of BDNF over 21 days while preserved the bioactivity of BDNF. Also, BDNF loading influenced the hydrogel nanostructure resulting in aligned orientation of nanofibers. Injection of BDNF-loaded IKVAV PA hydrogel resulted in a considerable axon preservation and astrogliosis reduction at 6 weeks post-injury without showing any inflammatory reaction. However, the BBB score was not statistically different between different treatment groups. Conclusion: Although the locomotor functional recovery was not observed in this study, the axon preservation and minimal inflammation in animals treated with BDNF-incorporated hydrogel indicate the potentiality of the designed intervention for further evaluations in the path of developing efficient therapies for severe spinal cord injury.